2x+4=5-6x

Simple and best practice solution for 2x+4=5-6x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x+4=5-6x equation:


Simplifying
2x + 4 = 5 + -6x

Reorder the terms:
4 + 2x = 5 + -6x

Solving
4 + 2x = 5 + -6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6x' to each side of the equation.
4 + 2x + 6x = 5 + -6x + 6x

Combine like terms: 2x + 6x = 8x
4 + 8x = 5 + -6x + 6x

Combine like terms: -6x + 6x = 0
4 + 8x = 5 + 0
4 + 8x = 5

Add '-4' to each side of the equation.
4 + -4 + 8x = 5 + -4

Combine like terms: 4 + -4 = 0
0 + 8x = 5 + -4
8x = 5 + -4

Combine like terms: 5 + -4 = 1
8x = 1

Divide each side by '8'.
x = 0.125

Simplifying
x = 0.125

See similar equations:

| 16-3x=-4(4x+3) | | 4(x-8)/5=16 | | 2y+(6+y)=12 | | x-8=6x-13 | | B^5=368 | | 2x+3=51-2x | | 2x+18-4x+12=-6 | | -2=2+(.25)v | | 4(3+c)=3(c-5) | | (x-3).6(x+1)=65 | | 9+(-2)=4+t | | 7x+1=31+4x | | 0.60x+.05(4-x)=.10(-20) | | 3(2x+6)=-6 | | 2m-9-8m=27 | | 6-2(4-8x)=2(3x-5) | | 2.5=d-(20) | | x-(3x+7)=11 | | x-6=-12+2x | | 2.5=d-(.20) | | -9+5x=-5x+1 | | 6.8x-15.3+4.2x=6.4+12x | | b=85+(23)w | | x+8=5x+52 | | 7x+19+-2x=55 | | -3x-5=-47+4x | | 5m-2(4m-1)=-14 | | 10=3x-5x+6 | | x-5-8x=16 | | -14x-4(2x-5)=9 | | -x+6+2x=13 | | 18=8-6b |

Equations solver categories